Improving Multi-Topic Household Surveys for Better Transport Policy Analysis - Lebrand, Mathilde Sylvie Maria; Yin, Qiuyan (Washington, DC: World Bank, 2022)
Household surveys remain underutilized for understanding transport choices such as expenditure level and composition, the economic impacts of road accidents, and the economic and distributional impacts of environmental policies such as vehicle restrictions or fuel taxes. This paper reviews more than 30 Living Standards Measurement Study surveys conducted after 2010, non-Living Standards Measurement Study surveys, and two World Bank harmonized household survey databases, to compile and categorize an extensive list of transport-related questions. The paper discusses current limitations in using Living Standards Measurement Study household surveys. Most of the transport-related questions in the Living Standards Measurement Study survey collection are not harmonized across years and countries. Consistent and more detailed data on road accidents and the type and use of vehicles should be added to help design and evaluate road safety and climate policies. A standard set of guidelines and sample questions to be integrated into future household surveys is therefore provided.